Radial profiles of plasma density and poloidal rotation velocity measured by microwave reflectometry for different regimes of RF plasma production in “Uragan-3m” torsatron - Skibenko, A.I.; Berezhnyj, V.L.; Volkov, E.D.; Ocheretenko, V.L.; Kotsubanov, B.D.; Nazarov, N.I.; Nikol’skiy, I.K.; Pavlichenko, O.S.; Pinos, I.B.; Fomin, I.P.; Tsibenko, S.A. (Вопросы атомной науки и техники, 2000)
Studies on choice of optimized regimes of RF plasma production/heating in Uragan-3M were performed by using microwave reflectometry. Radial profiles of electron density and it fluctuation and poloidal rotation velocity have been measured for different RF antenna configurations and confining magnetic field direction. It was shown that plasma parameters are changing at magnetic field reversal. Best regime is that one when magnetic field direction is “normal” (that one at which magnetic configuration was “tuned” at magnetic surfaces studies). This regime is characterized by higher value of electron density and by higher value of poloidal rotation velocity shear.